Relationship Between Nutrition Knowledge And Fast Food Consumption With Obesity In Adolescents - Yohana Wulandari (CV. AFDIFAL MAJU BERKAH, 2026)
Obesity is a condition when a person's weight exceeds normal limits due to excessive accumulation of fat tissue in the body. WHO in 2022 stated that 8% of children and adolescents aged 5-19 years in the world are obese. This study aims to determine the relationship between nutrition knowledge and fast food consumption with obesity in adolescents. This study was written using a literature review method based on articles collected using the Google Scholar and PubMed search engines. The inclusion criteria for the articles used were articles published between 2015 and 2025, both international and national articles, accessible in full text, original research, and containing information related to the relationship between nutritional knowledge and fast food consumption with obesity in adolescents. Based on the search results, a total of nine articles related to the topic were obtained. Based on these articles, four out of six articles stated that there was no relationship between nutritional knowledge with obesity in adolescents. Meanwhile, three out of four articles stated that there was a relationship between fast food consumption with obesity in adolescents. The relationship between nutrition knowledge and fast food consumption with adolescent obesity is inconsistent. This happens because there are various factors that influence it..